Pengaruh Ukuran Perusahaan, Audit Tenure, Dan Profitabilitas Terhadap Audit Delay Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2017-2019 - Sulistiawati, Mayang; Amyar, Firdaus (Institut Bisnis dan Informatika Kesatuan, 2022)
This study aims to determine the influence of company size, audit tenure, and profitability on audit delay at banking companies which is listed in the Indonesia stock exchange beetween 2017-2019. In this study, researchers used purposive sampling techniques that produced 36 banking companies or 108 data to be sampled. The research method used is quantitative method with multiple linear regression analysis. The data is collected with documentation. The results of this study showed that simultaneously or together the size of the company, audit tenure, and profitability influenced the audit delay with a significance value smaller than 0.05 (0.000 < 0.05) and F calculated > F table (13,253 > 2.69). Partially the size of the company negatively affects audit delays with a value of 0.000 less than 0.05 (0.000 < 0.05) and t count > t table (-4,605 > 1.9830). While variable audit tenure has no effect on audit delay with significance value greater than 0.05 (0.336 > 0.05) and t calculate < t table (0.907 < 1.9830) and profitability had no effect on audit delays with significance greater than 0.05 (0.280 > 0.05) and t count < t tables (-1,085 < 1.9830). Keywords: Company Size, Audit Tenure, Profitability, Audit Delay.